2017
DOI: 10.18203/2320-6012.ijrms20174116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of babies with meconium stained amniotic fluid

Abstract: Background: Meconium staining of amniotic fluid (MSAF) is a relatively common problem occuring in 10-25% of all deliveries. Meconium aspiration syndrome is more common in term babies than in preterm babies with rising frequency along with increase in gestational age of the fetus. Meconium stained amniotic fluid generally indicates sign of fetal distress. The objective of this study was to study clinical profile of meconium aspiration syndrome and the probable risk factors for meconium aspiration syndrome.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…are so many predisposing risk factors that promote the passage of meconium into the amniotic fluid in utero like utero-placental insufficiency, maternal hypertension, cord around neck, oligohydramnios, diabetes mellitus, heavy smoking, post-term pregnancy and intra uterine growth restriction, ante-partum haemorrhage and anemia. 4 Outcome of MAS mainly depends on type of meconium that is thin or thick, amount of meconium aspirated and perinatal care offered to the baby during delivery, planned team approach to MSAF babies, proper perinatal care has changed the morbidity and mortality of MAS. 5 The aim of the study study was to investigate clinical profile of MAS, its risk factors and severity among newborns at our institute.…”
Section: Introductionmentioning
confidence: 99%
“…are so many predisposing risk factors that promote the passage of meconium into the amniotic fluid in utero like utero-placental insufficiency, maternal hypertension, cord around neck, oligohydramnios, diabetes mellitus, heavy smoking, post-term pregnancy and intra uterine growth restriction, ante-partum haemorrhage and anemia. 4 Outcome of MAS mainly depends on type of meconium that is thin or thick, amount of meconium aspirated and perinatal care offered to the baby during delivery, planned team approach to MSAF babies, proper perinatal care has changed the morbidity and mortality of MAS. 5 The aim of the study study was to investigate clinical profile of MAS, its risk factors and severity among newborns at our institute.…”
Section: Introductionmentioning
confidence: 99%
“…16 About 5% of the babies born through meconium stained amniotic fluid develop meconium aspiration syndrome and the mortality rate of these babies vary from 4-7%. 17 In deliveries complicated with MSAF, there is an increased risk of caesarean section, chorioamnionitis and puerperal sepsis along with higher morbidity and mortality in mother while the unfavorable outcomes in neonate include increased risks of birth asphyxia and fetal distress, low Apgar scores, increased incidence of neonatal intensive care unit (NICU) admission, meconium aspiration syndrome and early neonatal death. 18,19 Meconium stained amniotic fluid is really alarming for both obstetrician and pediatrician and thus taking the risks into consideration, this study was done to identify the associated risk factors of meconium stained deliveries and compare the perinatal outcome in deliveries complicated by meconium staining versus clear liquor.…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant association between low APGAR score at 1 min and the development of MAS which is similar to the present study. 16 The study done by Viraraghavan VR et al, showed that 3% of vigorous babies and 21.7% of nonvigorous babies developed MAS, which showed statistical significance between non-vigorous neonates and development of MAS (p <0.001). 11 The study done by Gurmeet et al showed that 33% of the cases with MAS expired and 67% of cases with MAS were discharged, which is almost similar to the present study.…”
Section: Discussionmentioning
confidence: 92%